Українці серед вищого командного складу збройних сил СРСР у роки німецько-радянської війни - Якубець, О. (Український історичний журнал, 2018)
За допомогою програмного забезпечення було сформовано та завдяки використанню кількісної методології проаналізовано перелік командувачів фронтів, армій, начальників штабів фронтів, командирів корпусів Червоної армії, усього 1106 осіб. Із них українці становили 133, або ж 12%, що на понад 6% менше частки представників цієї національності у структурі населення СРСР періоду німецько-радянської війни 1941–1945 рр. Водночас продемонстровано тотальне домінування росіян на вищих командних посадах – 77% за їх загальносоюзної частки 58%. Зроблено висновок про свідомий підхід радянського керівництва до формування вищого ешелону воєначальників. Наголошено на відсутності ґрунтовних досліджень із цієї теми в радянській та пострадянській історіографіях, як і публічної статистики стосовно представників різних етносів СРСР у складі збройних сил цієї країни загалом. Приділено увагу питанням визначення національності в умовах радянської юридичної системи та повноти статистики загальних переписів населення. Подано короткі біографічні довідки ґенералів, українців за походженням, котрі командували фронтами й арміями. The article is devoted to the question of the ethnic composition of the generals of the Red Army during the period of the German-Soviet war of 1941–1945. With the help of computer software, a corresponding list was compiled with the use of quantitative methodology. This included commanders of the fronts and armies, chiefs of the headquarters of the fronts, corps commanders – in all 1106 persons, of which 133 were Ukrainians, or 12%, which is more than 6% less than the share of representatives of this ethnic group in the structure of the population of the Soviet Union in the mentioned historical period. At the same time, with the help of statistical calculations, total dominance of Russians in command positions in the acting army was demonstrated – 77% with their all-Union share of 58%. The conclusion is made of a conscious imperial approach of the Soviet leadership to the formation of a higher echelon of commanders. It was stated that there was no conscious research on this subject in Soviet and post-Soviet historiography, and in the same way as public statistics on the representatives of ethnic groups of the USSR as part of the Red Army as a whole. The attention was also paid to the problem of determining the ethnicity in the conditions of the Soviet legal system and the question of the completeness of the census statistics of the population of the USSR. Brief profiles for Ukrainians who were at the head of the fronts and armies were given.